Representasi Dogma Orang Tua dalam Film Ngeri-Ngeri Sedap: Analisis Semiotika Roland Barthes - Affandi Salim Lubis; Rahmat Hidayat (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Films not only function as entertainment media, but also as cultural texts that represent values, ideologies, and social relations in society. This study aims to reveal the representation of the dogma